Putrajaya People Bureau - Ismail, Sumarni; Jaafar, Mohamad Fakri Zaky (American-Eurasian Network for Scientific Information, AENSI Publications, 2015)
It should be pointed out that the concept of citizenship has long been a dispute and value-laden one in a democratic theory. To some, citizenship has implied a set of individual rights, while to others it is seen as a broader set of social and civic responsibilities. Citizenship as participation can be seen as representing an expression of human agency in the political arena. It is broadly defined rights enable people to act as agents. For the last twenty years, the concept of participation has been widely used in the discourse of development. The concern with participation in social change process is commonly dated back to 1960s-1970s, building on the work of South American pioneers of participatory approaches to social transformation. For much of this period, the concept has referred to participation in the social area, in the community or in development projects. Increasingly, however, the concept of participation is being related to rights of citizenship and to democratic governance. Linking citizen participation to the state at this local grassroots level raises fundamental and normative questions about the nature of democracy and about the skills and strategies for achieving it. The purpose of citizen group activity is to influence public policy decision making. Governance is not only for specialists and government officials. Government actors need to open up for more transparent and responsive decision –making. Without transparency, citizen participation is poorly informed and less effective.